Topical Mitomycin C Application Following Surgical Excision in Canine Oral Papilloma: A Case Report - Jungyeon Yong; Myeongjee Kwon; Haerin Yoon; Sungin Lee; Kyung‐Mee Park (Veterinary Medicine and Science)
ABSTRACT Canine oral papillomatosis, caused by canine papilloma virus 1, is a benign condition primarily affecting young or immunosuppressed dogs. While most cases regress spontaneously, severe cases often require surgical intervention due to extensive lesions and associated discomforts. However, surgical excision is associated with a high risk of recurrence, necessitating adjuvant therapies. This report presents the case of a 1‐year‐old German Shepherd with severe oral papilloma unresponsive to prior treatments, managed through surgical excision followed by topical mitomycin C (MMC) application. MMC, applied intraoperatively and during follow‐up, effectively prevented recurrence over a 1‐year period. This case demonstrates the potential of MMC as an effective adjuvant therapy for severe canine oral papillomatosis, providing a novel approach in veterinary medicine.